PERSEPSI PENGUNJUNG TENTANG KENYAMANAN RUANG TERBUKA HIJAU (RTH) TAMAN IMAM BONJOL PADANG - Defrina, Eliza; Hermon, Dedi; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
This study aim getÂ  information, analizing and description of data about visitor perseption of Imam Bonjol Padang green area comfort, and analizing this study in viewing of 1) visitor perseption of imam Bonjol Padang green area in term of student brame 2) visitor perseption of Imam Bonjol Padang green area in term of road singers 3) visitor perseption of about comforttable in Imam Bonjol Padang green area. This study is quality study with interview technical. To answer this problem use primary and secondary data. Primary data collecting from observation, interview and discussing wite informan relevant parties and documentasi thet get from relevant parties.Â  This study show: 1) generally visitor not feel comfortable with student brand. Because they feel thereeatenedÂ  with student brand in Imam Bonjol padang green area people hopee local government attention such asÂ  talk came imam bonjol Padang green area with pamong praja police banned student attend this area with uniform 2) visitor not feel comfortable with road singer in Imam Bonjol Padang green area because they are not public and ofher forcing visitor it visitor dontât give them money. The road singer also donât hopee identification that can not be managed properlyÂ  and 3) visitors are less comfortable with the presence of Imam Bonjol traders in Taman Padang, due to hygiene and cleanliness of the park baranag merchandise Imam Bonjol kurarang support visitor comfort.